2013
DOI: 10.1021/jp406062b
|View full text |Cite
|
Sign up to set email alerts
|

Binary and Ternary Phase Behaviors of Short Double-Chain Quaternary Ammonium Amphiphiles: Surface Tension, Polarized Optical Microscopy, and SAXS Investigations

Abstract: A series of short chain dialkyldimethylammonium amphiphiles ([DiC(n)][X] and [DiC(n)]2[X] with n = 6, 8, or 10) has been investigated as a function of the nature of the counteranion [X] (Cl(-) and Br(-) as classical references and MoO4(2-) and WO4(2-) as catalytic anions). Critical aggregation concentrations (CACs) in water were determined by surface tension measurements, and the binary phase diagrams of the surfactant/water systems were established using polarized optical microscopy (POM) and small angle X-ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Previous work has indicated that double-tailed cationic surfactants have been widely used as fabric softeners, antimicrobials, and antistatic agents [20] in many formulations because of their strong absorbability onto negative surfaces. APG and didecyldimethylammonium chloride (DDAC) mixtures, combining the advantages of pure APG and DDAC, are of particular interest and importance in the development of multi-functional disinfection and washing products [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has indicated that double-tailed cationic surfactants have been widely used as fabric softeners, antimicrobials, and antistatic agents [20] in many formulations because of their strong absorbability onto negative surfaces. APG and didecyldimethylammonium chloride (DDAC) mixtures, combining the advantages of pure APG and DDAC, are of particular interest and importance in the development of multi-functional disinfection and washing products [21][22][23][24].…”
Section: Introductionmentioning
confidence: 99%
“…All the solutions were prepared with Ultrapure water (Millipore water, σ = 72.0 mNÁm −1 at 25 C). The surface tension was measured as reported in previous works (Hong et al, 2013). was prepared.…”
Section: Surface Tension Measurementsmentioning
confidence: 99%
“…16,21 While numerous amphiphile/IL/co-solvents have been investigated, the vast majority are microemulsions where the IL has been used as the amphiphile, the polar phase or as the nonpolar phase. [39][40][41][42] We previously used a high-throughput approach to characterize a broad range of aqueous, non-stoichiometric PIL solvents in terms of surface tension, apparent pH and liquid nanostructure, which are the properties strongly affecting the ability of a solvent to promote self-assembly. 43 Our findings showed that the selected solvent properties can be tailored through varying the water content as well as the nonstoichiometry, and general trends for each solvent property were obtained.…”
Section: Introductionmentioning
confidence: 99%